2015
DOI: 10.1111/pbr.12241
|View full text |Cite
|
Sign up to set email alerts
|

Implications of early selection for grain colour on iron and zinc content and productivity of common bean

Abstract: Brazilian consumers prefer beans of the beige grain colour. Common beans help supply dietary requirements for iron and zinc. The objectives of this study were (i) to determine whether early selection for grain colour affects the iron and zinc content and the grain yield in common beans and (ii) if an association between these characteristics was found, to obtain lines of carioca‐type grains with a high iron and zinc content and good grain yield. We evaluated 96 F3:4, F3:5 and F3:6 progeny at two locations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 16 publications
6
16
0
3
Order By: Relevance
“…These values are comparable to the broad-sense heritability estimates of iron concentrations in Andean common bean seeds (Possobom et al, 2015) and Middle American common bean seeds (Jost et al, 2009;Teixeira et al, 2015). The narrow-sense heritability estimates varied from 19.04 to 45.29% in the crosses of Ouro Branco × Light Red Kidney and IAC Boreal × Light Red Kidney, respectively, suggesting difficulties in the fixation of this character with the advance of generations.…”
Section: Inheritance Pattern Heritability and Heterosissupporting
confidence: 68%
See 1 more Smart Citation
“…These values are comparable to the broad-sense heritability estimates of iron concentrations in Andean common bean seeds (Possobom et al, 2015) and Middle American common bean seeds (Jost et al, 2009;Teixeira et al, 2015). The narrow-sense heritability estimates varied from 19.04 to 45.29% in the crosses of Ouro Branco × Light Red Kidney and IAC Boreal × Light Red Kidney, respectively, suggesting difficulties in the fixation of this character with the advance of generations.…”
Section: Inheritance Pattern Heritability and Heterosissupporting
confidence: 68%
“…A continuous distribution of the iron and zinc concentrations in common bean seeds was previously described in early (Possobom et al, 2015) and advanced (Blair, Astudilo, Grusak, Graham, & Beebe, 2009;Cichy, Caldas, Snapp, & Blair, 2009;Blair et al, 2010b;Ribeiro et al, 2014b;Teixeira, Lima, Abreu, & Ramalho, 2015) generations in recombinants that were obtained from the crosses Andean × Andean, Andean × Middle American and Middle American × Middle American. These results affirm that the iron and zinc concentrations in common bean present quantitative inheritance in populations of low and high homozygosity, regardless of the gene pool, and that they oppose the initial hypothesis of Cichy et al (2005) regarding the monogenic control of the zinc concentration in common bean seeds.…”
Section: Inheritance Pattern Heritability and Heterosismentioning
confidence: 90%
“…Iron and zinc deficiencies affect about 40% and 33%, respectively, of the people in the world (The Word Bank, 2006). The potential of beans for biofortification for iron and zinc has been evaluated, and the obtained results are promising (Blair, 2013;Jost et al, 2013;Petry et al, 2015;Teixeira et al, 2015). Biofortification for potassium, phosphorus and copper has not been reported in the literature for beans.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the biofortification of beans for iron, zinc, potassium, phosphorus and copper is a promising practice to improve human's health. Common bean inbred lines with high iron and zinc concentrations in grains were obtained by plant breeding (Blair, 2013;Pereira et al, 2014;Teixeira et al, 2015). Preliminary studies showed that it was possible to increase phosphorus and copper concentrations in common bean grains in 19.17 and 46.78%, respectively, in F 2 generation Poersch et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation